"Over My Dead Body": Wives' Influence in Family Business Succession. (December 2021) - Cosson, Barbara; Gilding, Michael
The family business literature barely addresses wives' influence in family business succession. Where it does so, the result is often tokenistic, stereotypical, and imprecise. Drawing on 34 in-depth interviews, this article makes three contributions. First, it identifies wives' critical influence in family business succession through socialization across the life span of the family business; specifically, through normative, interactive, and experiential socialization. Second, it demonstrates the diverse dynamics and impact of wives' influence on family business continuity. Third, it highlights the particular significance of experiential socialization, whereby changing expectations of marriage and family life have amplified wives' influence in succession outcomes.